COOPERATIVE LANGUAGE LEARNING IN SPEAKING CLASS - Liya Umaroh (Jurnal Inovasi Penelitian, 2022)
The purpose of this study is to describe the implementation of Cooperative Language Learning in speaking class during online class. Several challenges regarding technology-based teaching during this such as technology is isolating, learner interaction is limited, boredom, and low motivation. Cooperative language learning is one of teaching strategy that could be implemented in online class. a teaching and learning strategy that emphasizes shared attitudes or behavior in working or helping among students. Descriptive qualitative used in this study with sample from student on the first semester. It can be expressed that by implementing cooperative language learning in speaking class showed great enthusiasm from all the students. Through this method, Cooperative learning can develop the ability to express ideas or ideas with words verbally and compare them with other friends ideas, aware of all limitations and accept all differences, empower each student to be more responsible in learning develop students' ability to test their own ideas and understanding, receive feedback., and nteraction during the cooperative can increase motivation and provide stimulation to think.